THE EFFECT OF ESTAFET WRITING TECHNIQUE ON WRITING RECOUNT TEXT AT GRADE X STUDENTS OF SMA SWASTA HARAPAN PADANGSIDIMPUAN - Siregar, Desy Ilmedianti (jurnalalfa, 2024)
This research aimed to know the effect of using Estafet Writing Technique on writing Recount Text at grade X Students of SMA Swasta Harapan Padangsidimpuan. In this research, the researcher used one-group pretest-posttest design, there was not control group. The researcher gave pre-test to student, then, researcher gave the students’ treatment about writing Recount Text with Estafet Writing Technique. After treatment is given, researcher gives the student post-test. The population in this research were the students of SMA Swasta Harapan Padangsidimpuan. The researcher used purposive sampling were takes class of X IPA 1 as the sample of this research. The total of students in this class was 23 students. The score of students' before using Estafet Writing Technique was 56.04 and it was categorized "fair". While the mean score of student's after using Estafet Writing Technique was 78.91 and it was categorized "good". The result of both t-test was 14.350 and t-table was 1.717, it means that there is an effect of using Estafet Writing Technique on Writing Recount Text at Grade X Students of SMA Swasta Harapan Padangsidimpuan.